ANALISA PERILAKU KONSUMEN BRAND SWITCHING SMARTPHONE - Setiyawan, Setiyawan (DINAMIKA DOTCOM, 2016)
Brand switching has an internal factor and external factor. Customer dissatisfaction and the desire seeking for variation are examples for internal factor. The need for seeking a variation (variety seeking) and the effect of promotion and price are examples for external factor. Positive perception and love attitude for brand product that had been purchased and used can reflect consumer personality. Statistical test in this research shows that the direct effect of internal and external factors in brand switching has coefficient value 0.283 and statistically significant in Î± level = 0.05 that show by significant t value 0.000 (smaller than Î± = 0.05). Meanwhile, the indirect effect of internal and external factors through quality perception is (0.524 x 0.602) = 0.315. The calculation results can show that direct influence of internal and external factors variable is smaller than indirect influence of internal and external factors through quality perception. This results indicate that quality perception variables can be used as intervening variable. It means that quality perception can strengthen (moderating) the relationship between internal and external factors with brand switching, because the students feel that a good smartphone quality perception is in accordance with customer desires and expectations. Â Key words: Brand Switching, Internal and External Factor, Quality perception